2013
DOI: 10.1007/s00702-013-1097-7
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortical inhibition in ADHD: modulation of the transcranial magnetic stimulation-evoked N100 in a response control task

Abstract: The N100 component, evoked by transcranial magnetic stimulation (TMS) and electroencephalography is associated with the activation of inhibitory cortical circuits and has recently been suggested as a potential marker of inhibition in attention-deficit/hyperactivity disorder (ADHD). The aim of the present ADHD study was to investigate the modulation of the TMS-N100 in go and nogo trials of a response control task considering stages of response preparation, activation, execution and inhibition. Eighteen children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Previous developmental TMS-EEG studies have focused on TEP in the N100 latency range and shown that N100 is increased in children compared with adults [Bender et al, 2005;D'Agati et al, 2014;Helfrich et al, 2012]. When using a suprathreshold stimulus intensity, TMS elicited a notably enhanced GMFP response in children compared with adults, with the adolescents' responses lying between those of children and adults.…”
Section: Motor Network Developmental Changes In the Time Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous developmental TMS-EEG studies have focused on TEP in the N100 latency range and shown that N100 is increased in children compared with adults [Bender et al, 2005;D'Agati et al, 2014;Helfrich et al, 2012]. When using a suprathreshold stimulus intensity, TMS elicited a notably enhanced GMFP response in children compared with adults, with the adolescents' responses lying between those of children and adults.…”
Section: Motor Network Developmental Changes In the Time Domainmentioning
confidence: 99%
“…Studies on TEPs in children are scarce and have solely focused on the N100 component [Bender et al, 2005;D'Agati et al, 2014;Helfrich et al, 2012;Jarczok et al, 2016]. In their pioneering article, Bender et al [2005] showed that TMS-evoked N100 undergoes maturational decline and could serve as a test of cortical integrity and inhibitory function in children.…”
Section: Introductionmentioning
confidence: 99%
“…The negative deflection of EEG at 100 milliseconds after a TMS pulse, termed the N100, is a proxy of cortical inhibitory processes 76-80 . Recent studies have shown N100 abnormalities in association with ADHD 808182 .…”
Section: Noninvasive Brain Stimulation In Adhdmentioning
confidence: 99%
“…There have been few TMS–EEG studies in children, and they have all described TEPs to motor cortex stimulation (Bender et al, ; D'Agati et al, ; Helfrich et al, ; Jarczok et al, ; Määttä et al, ). The results from these studies indicate that the TMS‐evoked N100 component, the most prominent TEP after motor cortex stimulation, declines with maturation and could serve as a test of cortical inhibitory function in children (Bender et al, ; D'Agati et al, ; Helfrich et al, ). Moreover, these results demonstrate that interhemispheric signal propagation between motor cortices increases as a function of age (Jarczok et al, ; Määttä et al, ) and that the complexity of TEP morphology increases and signal spreading facilitates within ipsilateral and contralateral cortices, reflecting developmental changes in motor cortex functional connectivity (Määttä et al, ).…”
Section: Introductionmentioning
confidence: 99%